MARKET BASKET ANALYST BASED ON WEBSITE USING ECLAT ALGORITHM (CASE STUDY POLA PHARMACY) - Lawrence, Edgar; Mulyawan, Bagus; Perdana, Novario Jaya (Jurnal Ilmu Komputer dan Sistem Informasi, 2020)
Market basket analyst is a data mining technique to discover associations between datasets. Association rule mining identifies a relationship between a large set of data item. When a large quantity of data is constantly obtained and stored in database, several industries are becoming concerned about mining association rules from their databases. Market basket analysis examines customer buying patterns by identifying associations among various items that customers place in their shopping baskets. It is helpful to examine customer purchasing behaviour and assists in increasing sales. So this system is intended to develop a system for market basket analysis on Pola Pharmacy which generate association rules among itemsets with the use of ECLAT (Equivalence Class Transformation) algorithm. This system supports the decision making process for a market expert.